2021
DOI: 10.1186/s12967-021-03099-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for cystic fibrosis: new tools for precision medicine

Abstract: The discovery of the Cystic fibrosis (CF) gene in 1989 has paved the way for incredible progress in treating the disease such that the mean survival age of individuals living with CF is now ~58 years in Canada. Recent developments in gene targeting tools and new cell and animal models have re-ignited the search for a permanent genetic cure for all CF. In this review, we highlight some of the more recent gene therapy approaches as well as new models that will provide insight into personalized therapies for CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 152 publications
0
26
0
4
Order By: Relevance
“…Gene therapy and gene editing offers great hope for the treatment of a monogenic disease such as CF as these approaches would mean a potentially permanent cure (reviewed in [ 152 , 153 ]). In the case of gene therapy, although preclinical studies evidenced some success in cell and animal models, results from clinical studies have evidenced several difficulties, namely targeting the correct cell population in a proportion enough to translate into clinical benefit or overcoming the mucus barrier, limiting the number of studies that have in fact aimed at developing gene therapy approaches for CF patients [ 154 ].…”
Section: Molecular Mechanisms Of Disease – How Do Cftr Mutations Caus...mentioning
confidence: 99%
“…Gene therapy and gene editing offers great hope for the treatment of a monogenic disease such as CF as these approaches would mean a potentially permanent cure (reviewed in [ 152 , 153 ]). In the case of gene therapy, although preclinical studies evidenced some success in cell and animal models, results from clinical studies have evidenced several difficulties, namely targeting the correct cell population in a proportion enough to translate into clinical benefit or overcoming the mucus barrier, limiting the number of studies that have in fact aimed at developing gene therapy approaches for CF patients [ 154 ].…”
Section: Molecular Mechanisms Of Disease – How Do Cftr Mutations Caus...mentioning
confidence: 99%
“…Organoids can serve as a good platform for evaluating gene therapy, in which gene editing technologies are used to repair genetic deficiencies in patients. 311 , 436 , 437 For example, the use of CRISPR gene editing technology to correct CFTR mutations in intestinal organoids of CF patients has shown that gene repair can correct the CFTR locus in patient-derived CF organoids and restore the normal response of organoids to forskolin treatment. 438 Organoids can also be used as an alternative test model for FMT therapeutic strategies.…”
Section: Digestive System Organoid Models and Precision And Personali...mentioning
confidence: 99%
“…CRISPR-based gene editing approaches have been explored to correct certain CFTR mutations in cultured airway basal cells, iPS cells, and advanced cellular models, such as organoid cultures derived from patients with CF ( Ensinck et al, 2021 ; Lee et al, 2021 ). HDR-based CFTR corrections have demonstrated the capacities to correct missense or nonsense mutations in exons, to ablate splice mutations, and to insert “super exons” from the DNA donor template provided along with the CRISPR components ( Schwank et al, 2013 ; Firth et al, 2015 ).…”
Section: Gene Editingmentioning
confidence: 99%
“…New animal models and more efficacious gene transfer agents have been developed to move the field in the path to success. Several recent excellent review articles have summarized and discussed the lessons and achievements from the last 3 decades ( Cooney et al, 2018a ; Donnelley and Parsons, 2018 ; Yan et al, 2019 ; Tang et al, 2020a ; Allan et al, 2021 ; Lee et al, 2021 ). In this review, after a brief description of the lessons learned from the previous unsuccessful clinical trials of CF gene therapy in an alignment with recent progress in animal models and viral vectors as tools of gene delivery, we will focus on the major challenges to the implementation of the gene therapy for CF lung disease.…”
Section: Introductionmentioning
confidence: 99%